The epidemiology of malaria in Elazig between 1996 and 2004 - Kuk, Salih; Ozden, Mehmet; Kaplan, Mustafa (My University, 2006)
Malaria is a very important disease both for the world and Turkey. In this retrospective study, we investigated malaria using the data provided by The Health Administration of Elazig between 1996 and 2004. A total of 79,458 blood smears were examined during this 9-year period and malaria was found in 200 (0.25%). Except for one case of foreign origin infected with Plasmodium malaria, all of the cases were caused by Plasmodium vivax. All patients were imported cases who had come to Elazig from other regions for different reasons. We hope that our study contributes to the epidemiology of malaria and its prevention.
Elazi?'da 1996-2004 yillari arasinda sitma epidemiyolojisi.
Keywords: Adolescent; Age Distribution; Child; Child, Preschool; Humans; Infant; Infant, Newborn; Malaria, Vivax; Retrospective Studies; Turkey; adolescent; age distribution; article; child; human; infant; newborn; Plasmodium vivax malaria; preschool child; retrospective study; Turkey (republic)